1996
DOI: 10.1002/j.1552-4604.1996.tb04167.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Anabolic Steroids in Weight‐Trained Subjects

Abstract: The effects of large doses of anabolic steroids on 24-hour blood pressure, cardiac structure and function, and lipid profiles were studied in 10 body builders using anabolic steroids and 14 body builders who did not use steroids (control subjects). All subjects underwent noninvasive 24-hour blood pressure monitoring, echocardiography, Doppler analysis of transmitral flow, and analysis for lipoprotein and gonadotropin levels. Anabolic steroid users were studied at the end of a steroid cycle and after a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 37 publications
1
35
0
9
Order By: Relevance
“…This increase in diastolic blood pressure was reported from 74 to 86mm Hg after 10 weeks of high-dose AAS use. Blood pressure measured by an ambulatory monitor over a 24-hour period showed similar results in AAS users and controls, although chronic AAS use causes an abnormal nocturnal physiological dipping (13). This is in contrast to a more recent robust study showing that AAS is not associated with significant effects on arterial structure and function, but however did affect vascular reactivity and arterial thickness (14).Another prospective study did not show statistically significant alterations in blood pressure, even in those self-administering supra-therapeutic doses of AAS for periods of up to 16 weeks (15).…”
mentioning
confidence: 59%
“…This increase in diastolic blood pressure was reported from 74 to 86mm Hg after 10 weeks of high-dose AAS use. Blood pressure measured by an ambulatory monitor over a 24-hour period showed similar results in AAS users and controls, although chronic AAS use causes an abnormal nocturnal physiological dipping (13). This is in contrast to a more recent robust study showing that AAS is not associated with significant effects on arterial structure and function, but however did affect vascular reactivity and arterial thickness (14).Another prospective study did not show statistically significant alterations in blood pressure, even in those self-administering supra-therapeutic doses of AAS for periods of up to 16 weeks (15).…”
mentioning
confidence: 59%
“…Several studies demonstrated an increase in left ventricular end diastolic volume, left ventricular mass and/or worsening diastolic function [11][12][13], while other studies demonstrated no cardiovascular changes with anabolic steroid use [14][15][16]. However, in bodybuilding, the doses used are often 10-100 times the therapeutic dose; in one report involving 24 weight lifters, the lowest dose was 350% of the usual therapeutic dose [17].…”
Section: Discussionmentioning
confidence: 99%
“…Poor visualization of the right ventricle, a poorly defined endocardial surface, irregular right ventricular geometry, and limited reproducibility of exercise studies are important limitations of echocardiography in evaluating the left and right ventricle [26]. Cardiac exercise CT has been shown to have excellent sensitivity and specificity for detecting coronary disease and for assessing changes in both right and left ventricles [11][12][13][14][15]27,34]. CT also allows clear apical delineation, and breast shadows, obesity, the diaphragm or bowel do not cause attenuation, and excellent reproducibility has been demonstrated, with interstudy, intraobserver and interobserver variations were 0.01±1.4, 0.06±2.0 and 0.28±2.1% respectively [14,28,29,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die vorliegenden Befunde unter AAS sind uneinheitlich. Es wird sowohl über eine unveränderte [21,24,45,83,101,110] als auch über eine eingeschränkte diastolische linksventrikuläre Funktion [20,57,80,86,105,106] berichtet. Die diskrepanten Befunde lassen sich am ehesten methodisch erklären.…”
Section: Systolische Und Diastolische Linksventrikuläre Funktionunclassified